Organic photovoltaics for low light applications - Steim, Roland; Ameri, Tayebeh; Schilinsky, Pavel; Waldauf, Christoph; Dennler, Gilles; Scharber, Markus; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Here we report on organic photovoltaics (OPV) suitable for low light applications. In this paper, we illustrate the impact of R and R for indoor and outdoor applications. In addition, we propose a simple physics approach to predict the behavior of organic solar cells under various illumination intensities through electrical modeling. The combination of simulation and modeling allows to define a set of design rules for OPVs under low light illumination. The performance of various organic solar cells under low light intensity is compared with our predictions and excellent correlation is found. OPV shows high performance under low light conditions. © 2011 Elsevier B.V. All rights reserved.
Keywords: Indoor; Low light; OPV; Organic photovoltaics; Shunt resistance; Simulation